The clinical application and laboratory management of molecular genetic diagnosis in children's hospital - Wenjie Bao; Qihua Fu; Xiaoqing Zhang; Xi Mo; Tingting Yu (Wiley, 2024)
Abstract Background Molecular diagnostic technology is the foundation of precision medicine, which has the advantages of good specificity, high sensitivity, strong targeting, rapiddiagnosis, etc. It has a wide range of applications in the field of pediatrics. However, molecular diagnostic technology is characterized by complicated experimental operation, high difficulty in data analysis and interpretation, in consistent standards among laboratories, and difficult standardization of technical processes. Enhancing the application value of molecular diagnostic technology in pediatrics and promoting the high‐quality development of the discipline requires careful consideration by relevant management and professionals. Methods This study firstly outlines the development history of molecular diagnostic technology. Then, it analyzes the application of molecular diagnostic technology in the field of pediatrics. Finally, it explores the countermeasures for the management of molecular diagnostic laboratories. Results This study highlights the importance of molecular diagnostic technology in providing information and decision‐making basis for disease prevention, prediction,diagnosis, treatment and regression. It has a wide range of applications in the molecular diagnosis of pediatric hereditary diseases, malignant tumors and infectious diseases. In addition, the countermeasures for the management of molecular diagnostic laboratories are proposed from the five aspects of laboratory, personnel team construction, standardized management,multidisciplinary cross‐discipline, research and translation, safety managementand ethical supervision, and management upgrading and modernization. Conclusions Molecular diagnostic technology, as the basis of precision medicine, has become one of the important frontier fields in the development of contemporary pediatric medicine. Enhanced laboratory capacity in molecular diagnostic techniques can improve outcomes in the prevention, prediction, diagnosis, treatment, prognosis and research of pediatricdiseases, and lay the groundwork for child healthcare.